Application of 5-aminolevulinic acid promotes ripening and accumulation of primary and secondary metabolites in postharvest tomato fruit - Wang, Junwen; Yuan, Hong; Wu, Yue; Yu, Jihua; Ali, Basharat; Zhang, Jing; Tang, Zhongqi; Xie, Jianming; Lyu, Jian; Liao, Weibiao (Frontiers in Nutrition, 2022)
5-Aminolevulinic acid (ALA) plays vital roles in promoting plant growth, enhancing stress resistance, improving fruit yield and quality. In the present study, tomato fruit were harvested at mature green stage, sprayed with 200 mg L-1 ALA on fruit surface. During ripening, estimation of primary and secondary metabolites, carotenoids, chlorophyll contents and expression levels of key genes involved in their metabolism were carried out. The results showed that ALA significantly promoted carotenoids accumulation by up-regulating the gene expression levels of geranylgeranyl diphosphate synthase (GGPPS, encoding geranylgeranyl diphosphate synthase), phytoene synthase 1 (PSY1, encoding phytoene synthase), phytoene desaturase (PDS, encoding phytoene desaturase), and lycopene β-cyclase (LCYB, encoding lycopene β-cyclase), whereas decreased chlorophyll content by downregulating the expression levels of Mg-chelatase (CHLH, encoding Mg-chelatase) and protochlorophyllide oxidoreductase (POR, encoding protochlorophyllide oxidoreductase). Besides, the contents of soluble solids, vitamin C, soluble protein, free amino acid, total soluble sugar, organic acid, total phenol and flavonoid were increased in ALA-treated tomato fruit, but the fruit firmness was decreased. These results indicated that exogenous ALA could not only promote postharvest tomato fruit ripening, but also improve the internal nutritional and flavor quality of tomato fruit.